2007
DOI: 10.1007/s11095-007-9298-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carrier on Disposition and Antitumor Activity of Intraperitoneal Paclitaxel

Abstract: Our results indicate the important roles of drug carrier in determining the peritoneal targeting advantage and antitumor activity of IP treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
111
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 32 publications
3
111
0
Order By: Relevance
“…In our opinion, this slower clearance rate can be attributed to the aggregation of these nanoparticles to micrometer sized particles in the IP fluid. As has been suggested, these microparticles do indeed show a slower clearance rate from the IP cavity when compared to nanoparticles [59].…”
Section: Tailoring Delivery Systems For Ip Therapysupporting
confidence: 53%
“…In our opinion, this slower clearance rate can be attributed to the aggregation of these nanoparticles to micrometer sized particles in the IP fluid. As has been suggested, these microparticles do indeed show a slower clearance rate from the IP cavity when compared to nanoparticles [59].…”
Section: Tailoring Delivery Systems For Ip Therapysupporting
confidence: 53%
“…MPs were retained in the peritoneal cavity for a longer time period, but a high incidence of adhesions 2 weeks after injection of the MPs made them unsuitable for long term delivery to the peritoneum [61]. Similarly, Tsai et al examined the effect of carrier size on the disposition and anti-tumor activity of paclitaxel (PTX) [62]. In particular, PTX loaded gelatin MPs and NPs, as well as Cremophor micelles were systematically studied in mice bearing…”
Section: Biodistribution Of Nps Following Ip Injectionmentioning
confidence: 99%
“…The authors attributed this clearance profile to the dimensions they found for the lymphatic duct openings (known as stomata) on the diaphragm of mice, which ranged on average from 0.7 to 15.5 µm in length and 0.5 to 8.2 µm in width. Therefore, NPs smaller than these openings were rapidly cleared into the systemic circulation, while a more slow absorption occurred for MPs which were similar in size to the openings [62]. Also, Hirano and Hunt investigated the size effect on the peritoneal retention of liposomes of 48, 170, 460 and 720 nm in rats [63].…”
Section: Biodistribution Of Nps Following Ip Injectionmentioning
confidence: 99%
“…[26][27][28] NPs or micelles have shown rapid clearance from the peritoneal cavity. 29 Considering the advantages of polymeric thermosensitive hydrogels, in this study, Doc and LL37 were coloaded in polylactic acid (PLA)-Pluronic L35-PLA (PLA-L35-PLA) NPs (Doc+LL37 NPs), and then the Doc+LL37 NPs were dispersed in PLA-L64-PLA (number-average molecular weight [M n ] 4,500) thermosensitive hydrogel to prepare Doc+LL37 NPs-hydrogel composites, and treatment with Doc+LL37 NPs-hydrogel composites in colorectal peritoneal carcinomatosis HCT116 models was evaluated. Our findings indicated that the NP-hydrogel composites improved antiangiogenesis and antitumor activity both in vitro and in vivo, and might have great potential clinical application.…”
Section: Introductionmentioning
confidence: 99%